TV news and its reflection on the level of anxiety in the elderly - Dawood, Dhuha S.; Khazall, Adulnabi (Al-Adab Journal, 2021)
The research covered (TV news and its reflection on the level of anxiety in the elderly) By Dhuha S. Dawood An important aspect related to the media aspect and its psychological and social effects on the elderly audience in a way that shows the effect of television news and how this is reflected on the psychological side, especially the anxiety of the elderly group, which is one of the most important age groups that are related to their surroundings and carry many ideas and experiences and affect those around them, and the research is presented within A systematic scientific framework by applying the theory of media dependence in the survey of elderly people in the capital, Baghdad, and building an anxiety scale commensurate with the research topic. And because of the importance of research in the scientific aspect, which represents a qualitative addition to media, psychological and social studies, and to reach the research objectives, the study subjected the period from (1/10/2019 to 1/1/2020) for the survey study of the scale of anxiety for the elderly over the age of fifty-five years. And more than women and sixty years and over are men in the capital, Baghdad, according to the classification of the Iraqi Social Welfare Law (26) for the year 1985 and by the accidental in-kind method. The results indicated the presence of moderate anxiety in the elderly, and there were no differences in demographic factors in terms of gender (sex) and age levels, but the results indicated that there were differences between the level of anxiety according to the academic achievement variable, as the higher the academic achievement, the lower the level of anxiety in this group of The elderly and vice versa, and there are differences according to the profession variable, the higher the level of anxiety resulting from exposure to television news, while the variables (retired, employee, and housewife) were not affected by exposure to television news.